Analyzing Non-Verbal Communication in Instructors' Classroom Demonstration - Wilda Asrina (Barkah Publishing, 2025)
Non-verbal communication (NVC) is a fundamental yet often under-analyzed dimension of instructional delivery in English as a Foreign Language (EFL) contexts. This study examines how instructors employ non-verbal communication—specifically gestures, facial expressions, eye contact, posture, and spatial dynamics—during classroom demonstrations, and how these cues shape student comprehension and engagement. Employing a qualitative descriptive design, data were gathered through non-participant classroom observations and semi-structured interviews with EFL teachers at a vocational high school in Banda Aceh, Indonesia. Thematic analysis revealed four primary dimensions: (1) a dual-operating mechanism of instinctual and intentional NVC usage; (2) NVC acting as a multimodal pedagogical scaffold for abstract concepts; (3) dynamic teacher adjustments based on real-time student feedback; and (4) proxemics and posture serving as indicators of authority and approachability. The findings demonstrate that NVC is not merely an ancillary teaching aid, but a core pedagogical strategy that bridges linguistic gaps and enhances interactive learning. This research highlights the necessity of incorporating deliberate NVC training into language teacher education programs.